1982
DOI: 10.1021/bi00266a042
|View full text |Cite
|
Sign up to set email alerts
|

Specific stimulation of the T7 gene 6 exonuclease by the phage T7 coded deoxyribonucleic acid binding protein

Abstract: Bacteriophage T7 codes for a single-stranded DNA binding protein. This protein is the product of gene 2.5 and has been found previously to stimulate specifically the activity of the phage-coded DNA polymerase. We report here that the T7 DNA binding protein also stimulates the activity of the phage-coded exonuclease. The gene 6 exonuclease is a double-stranded DNA specific 5'-exonuclease that has been implicated in destruction of bacterial DNA, removal of RNA primers during DNA replication, genetic recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…(47) that showed that the first cleavage made by the exonuclease activity of gp6 at the 5Ј-terminus is not stimulated by gp2.5 because the substrate used in that study did not have an adjacent ssDNA region (47).…”
Section: Stimulation Of Gp6 Activity By T7 Gene 25 Ssdna-bindingmentioning
confidence: 90%
See 2 more Smart Citations
“…(47) that showed that the first cleavage made by the exonuclease activity of gp6 at the 5Ј-terminus is not stimulated by gp2.5 because the substrate used in that study did not have an adjacent ssDNA region (47).…”
Section: Stimulation Of Gp6 Activity By T7 Gene 25 Ssdna-bindingmentioning
confidence: 90%
“…The finding that E. coli ssDNA protein did not stimulate gp6 implies that there is an interaction of gp2.5 with gp6. However, no physical interaction between the two proteins was detected (47).…”
Section: Stimulation Of Gp6 Activity By T7 Gene 25 Ssdna-bindingmentioning
confidence: 96%
See 1 more Smart Citation
“…In other biological systems, a critical role of single strand DNA binding protein is to protect exposed single-stranded DNA from nuclease attack (2). In T7 the single strand binding protein enhances the activity of gene 6 exonuclease so that apparent nuclease degradation is actually more pronounced with the gene 2.5 protein than without it (46). Thus, available data provide no evidence to suggest that excessive DNA degradation causes the inhibition of recombinational repair associated with gene 2.5 inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the kinetics of ligation should be a measure of the extent of DNA looping. The gene 6 exonuclease of phage T7 hydrolyzes double-stranded DNA in a 5 0 to 3 0 direction (Roberts et al, 1982). A fixed amount of labeled DNA either by itself or after preincubation with just the monomers, or first preincubation with monomers followed by the dimers, was treated for the indicated time periods with DNA ligase at 12ºC.…”
Section: Optimal Incc-orif Looping Required the Presence Of Both Monomeric And Dimeric Repementioning
confidence: 99%